EDIBLE BIRD NEST AS MULTIPOTENTIAL AGENT - Effendy, Kgs. Mahendra (Majority, 2015)
Abstract Edible bird nest is a famous food since the 16th century in China. Aside from being a food, edible bird nest also serves as an alternative medicine. Edible bird nest containing proteins, fats, carbohydrates, iron, calcium, phosphorus, amino acids and others. Edible bird nest has a variety of functions in the human body. Bird nest can function as an antioxidant, tissue repair, anti-aging, and various other functions. So it needs further development in order to swallow nest can be widely used in the medical world. Keywords : anti-aging, antioxidant, edible bird nest, tissue repair Abstrak Sarang burung wallet merupakan makanan yang terkenal sejak abad ke-16 di Cina. Selain sebagai makanan, sarang burung wallet juga berfungsi sebagai obat alternatif. Sarang burung wallet mengandung protein, lemak, karbohidrat, zat besi, kalsium, fosfor, berbagai asam amino dan lain-lain. Sarang burung wallet memiliki berbagai fungsi dalam tubuh manusia. Sarang burung wallet dapat berfungsi sebagai antioksidan, proliferasi sel, anti-aging, dan berbagai fungsi lainnya. Sehingga perlu pengembangan lebih lanjut agar sarang burung wallet ini dapat digunakan secara luas dalam dunia medis. Kata kunci : anti-aging,antioksidan, perbaikan jaringan, sarang burung wallet